Mental health in later life : taking a life course approach - Milne, Alisoun (Ageing and the lifecourse., 2020)
Drawing together material from a number of different fields the book analyses the meaning and determinants of mental health amongst older populations and offers a critical review of the lifecourse, ageing and mental health debate.